The effectiveness of silvofishery system in water treatment in intensive whiteleg shrimp (Litopenaeus vannamei) ponds, Probolinggo District, East Java, Indonesia - Muhammad Musa; Evellin Dewi Lusiana; Nanik Retno Buwono; Sulastri Arsad; Mohammad Mahmudi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Musa M, Lusiana ED, Buwono NR, Arsad S, Mahmudi M. 2020. The effectiveness of silvofishery system in water treatment in intensive whiteleg shrimp (Litopenaeus vannamei) ponds, Probolinggo District, East Java Indonesia. Biodiversitas 21: 4695-4701. Whiteleg shrimp (Litopenaeus vannamei) is a popular aquaculture species in Indonesia due to its high market demand. It requires excellent water quality to ensure its growth rate and production. Therefore, intensive culture system is considered. However, the system threatens the sustainability of the adjacent environment and thus proper water treatment is necessary to increase the quality of water used in shrimp farming as well as the wastewater it produces. In this study, we explored the use of a silvofishery system that integrates mangroves into a pond as a potential solution to this issue. This study aimed to assess the effectiveness of the silvofishery system at treating water inputs and effluents of a whiteleg shrimp pond in Probolinggo District, East Java, Indonesia. Eight physicochemical water quality parameters and a phytoplankton community at four sampling sites during neap tide period were examined in this study. The effectiveness of the silvofishery system in increasing water quality was analyzed using analysis of variance (ANOVA), while the diversity of phytoplankton for biomonitoring was measured with the Shannon-Wiener diversity index (H’). The results showed that the mangrove effectively increased the quality of the water supply and wastewater in the intensive whiteleg shrimp pond-especially in terms of nutrient removal-as well as the biodiversity of its phytoplankton community. Other parameters such as TOM and ammonia also decreased, though this was not statistically proven.